Implementation of E-Government Through the Management of the Kertayasa Village Website in Kuningan - Ilham Arya Wiguna; Yanto Heryanto; Aghnia Dian Lestari (Salus Publica: Journal of Community Service, 2026)
Villages have been encouraged to use information technology to provide public services through the deployment of e-government as a result of advancements in digitalization within government. One of the main tools for providing administrative services and information online is a website, which promotes more responsive and transparent governance. The goal of this study is to examine how e-government is being implemented in Kuningan Regency through the administration of the Kertayasa Village website, with an emphasis on efficiency, effectiveness, accountability, and transparency. The selected methodology is descriptive qualitative, using methods for gathering data such observations, interviews, and documentation. Data validity is ensured by triangulation. Data analysis was conducted using the Miles and Huberman interactive model, The Miles and Huberman interactive model, which covers data reduction, data display, and conclusion drawing, was used to analyze the data. According to the study's findings, the village website has been utilized as a platform for public grievances, an information channel, for basic administrative services, and to publicize events. Procedures, service accessibility, public information transparency, and administrative accountability are all improved by this implementation. However, limitations in human resources for system management and the suboptimal utilization of the village website by the community remain challenges in optimizing the system therefore, capacity building for administrators and ongoing support are necessary.